Research on the factors influencing tourist loyalty to outdoor music festivals: an application of stimulus-organism-response paradigm - Zhu, Ning; Xu, Haochen; Zhang, Xi; Lu, Yuhui (Frontiers in Psychology, 2025)
IntroductionFollowing the COVID-19 pandemic, China's music festival market has rapidly recovered, attracting growing tourist interest. However, research on factors influencing tourist loyalty remains limited.MethodsThis study applies the Stimulus-Organism-Response (S-O-R) framework to examine loyalty formation among festivalgoers. Data were collected via a questionnaire from 673 attendees of the Shenyang Strawberry Music Festival. Structural equation modeling (SEM) was used for analysis.ResultsPerceived value and satisfaction significantly impact loyalty, with satisfaction showing a stronger effect. Existential authenticity and experience quality enhance emotions, perceived value, and satisfaction. Emotions do not directly influence loyalty but have indirect effects via value and satisfaction.DiscussionFindings suggest that enhancing existential authenticity and experience quality can indirectly build loyalty. The study offers strategic insights for festival organizers seeking to sustain tourist engagement post-pandemic.